The interrelationships between football fans’ psychological connection to a team, perception of sponsorship and sponsorship response in the context of new team and new sponsor - Kadir Yağız (ROL Spor Bilimleri Dergisi)
This paper aims to propose an integrated model to evaluate sponsorship effectiveness in newly organized professional football teams. To achieve this, the effects of fan identification as the psychological connection of sports fans with a sports team, on sponsorship perceptions, such as attitude towards the sponsor and brand image, and sponsorship response, such as purchasing intention, were examined. In addition, the mediating role of consumer sponsor perceptions in the relationship between fan identification and purchasing intention was tested. The data were gathered from 255 fans of Alagöz Holding Iğdır football club. Confirmatory factor analyses (Amos 23 IBM) and PROCESS analyses (SPSS) was conducted in statistics. The findings supported our model, which proposes that fan identification has a direct impact on sponsorship perceptions and response, and that sponsorship perceptions mediate the relationship between fan identification and sponsor response. The main contribution of this paper is the incorporation of fan identification, attitude towards sponsor, sponsor brand image, and purchase intentions within an integrated sponsorship model, and testing of their interrelations which have not been empirically tested in the context of a newly formed professional football team. Practical implications for both sports team marketers and sponsors are explained in the paper.